2021
DOI: 10.3389/fpsyg.2021.744618
|View full text |Cite
|
Sign up to set email alerts
|

Refining the Assessment of Entitlement in Romantic Relationships: The Sense of Relational Entitlement Scale—Revised (SRE-R)

Abstract: Objective: A subjective sense of entitlement is strongly evoked in the context of romantic relationships. A pathological sense of entitlement results from believing a partner should fulfill all one’s needs and wishes (inflated) or that the expression of genuine needs is illegitimate (restricted). This study aimed to validate a revised, improved version of the Sense of Relational Entitlement scale entitled the Sense of Relational Entitlement scale—Revised (SRE-R). We hypothesized it would have good factor struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…It seems that exposure to IPC during childhood may impair one’s future capacity to realistically appraise expectations from a romantic partner. Past research has indicated that restricted and inflated forms of entitlement are negatively associated with marital adjustment (Tolmacz & Mikulincer, 2011) and relationship satisfaction (George-Levi et al, 2014; Tolmacz et al, 2021a), and positively associated with divorce rates (Sanchez & Gager, 2000), selfishness, violence, and aggression in romantic relationships (Campbell et al, 2004; Wood, 2004). Our results suggest that IPC may be associated with a proneness to crises in couples’ relationships since it increases risk for an imbalanced sense of relational entitlement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that exposure to IPC during childhood may impair one’s future capacity to realistically appraise expectations from a romantic partner. Past research has indicated that restricted and inflated forms of entitlement are negatively associated with marital adjustment (Tolmacz & Mikulincer, 2011) and relationship satisfaction (George-Levi et al, 2014; Tolmacz et al, 2021a), and positively associated with divorce rates (Sanchez & Gager, 2000), selfishness, violence, and aggression in romantic relationships (Campbell et al, 2004; Wood, 2004). Our results suggest that IPC may be associated with a proneness to crises in couples’ relationships since it increases risk for an imbalanced sense of relational entitlement.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of romantic relationships, several studies have found pathological concern to be associated with higher levels of relationship conflict (Feeney & Collins, 2003) and lower levels of authenticity and relationship satisfaction (Tolmacz et al, 2021b, 2021a). The link between pathological concern and low authenticity is corroborated in this study and further linked to childhood IPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale offers scores for assertive entitlement (seven items), excessive entitlement (eight items), and restricted entitlement (three items). However, due to the lack of evidence regarding the link between assertive entitlement and relational satisfaction [ 28 ], only the excessive (e.g., “When my partner frustrates me, I contemplate ending the relationship”) and the restricted (e.g., “Sometimes I feel I am not good enough for my partner”) dimensions were used. Both scales showed adequate internal consistency.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the concept of sense of relational entitlement was developed, referring strictly to those expressions of entitlement appearing in the romantic domain, and it can be defined as the extent to which a person expects that their needs and wishes will be fulfilled by the romantic partner, and as a person’s affective and cognitive responses to a romantic partner’s failure to fulfill these needs and hopes [ 18 ]. Similar to the broader concept of psychological entitlement, relational entitlement can also have two expressions: one excessive (the individual believes that their needs must be fulfilled regardless of the needs or emotional state of their partner) and one restricted (the individual is unassertive, timid, and less self-assured in demanding to have their needs fulfilled) [ 18 , 28 ].…”
Section: Introductionmentioning
confidence: 99%